HUBUNGAN TEKANAN PANAS DENGAN DENYUT NADI PADA PEKERJA DI PT PERKEBUNAN NUSANTARA IV KEBUN BAH BUTONG TAHUN 2015 - malta indah aperos; lina tarigan; makmur sinaga (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT One of the work environments which cause the health disorder for workers is extreme heat exposure. A heat environment cause the additional load for heart in pumping blood an increases the pulse. PT Perkebunan Nusantara IV Bah Butong Plantation, is one of plantation businesses and factory in tea processing. In the drying station, the workers directly exposure by extreme heat work environment from drying machines. The study was an analytic survey with cross- sectional design. The population were 28 workers, and all of them were used as the samples, using total sampling technique. Bivariate analysis with chi square statistic test used to find out the correlation between heat stress and worker’s pulse. The measurement of heat stress was conducted by using Questtemp.It were found that 5 workers had heat stress qualify and 23 workers did not. The measurement of worker's pulse was conducted by using palpation method with stopwatch. It were found that before and after work, 6 workers had normal pulse and 22 workers had increase pulse. The result of statistic test showed that there was significant correlation between heat stress and worker's pulse in the workers at PT Perkebunan Nusantara IV Bah Butong Plantation, in 2015. It is recommended that the workers drink plain water as frequently as possible in order to return the lost of body liquid during working. Using the uniform which consist of the materials that are not produce heat is quite recommended. Keywords: Workers, Drying Station, Heat Stress, Pulse